The IMPACT OF INCUBATION PERIOD AND TEMPERATURE ON HORSE MILK AGAINST MILK QUALITY AND TOTAL LACTIC ACID BACTERIA (LAB) - Fairuz Nanda Marhabanaz; Haryanto; Ajeng Erika Prihastuti Haskito; Titisari, Nurina (Veterinary Biomedical and Clinical Journal, 2025)
Horse milk has a slightly higher lactose content than cow's milk. Lactic Acid Bacteria (LAB) fermented lactose in horse milk, causing a lower pH change. Many factors, including temperature and environment, are influencing LAB growth. This study was conducted to determine the effect of differences in incubation time and temperature on the increasing number of lactic acid bacteria and milk quality. The horse milk samples used in this study originated from four Sumbawa wild horses in the first lactation period. This study conducted two experiments, In the first experiment, all samples were incubated at 37oC, further testing was carried out at 0, 12, 24, 36, and 48 hours. In the second experiment, all samples were incubated for 24 hours with different incubation temperatures, i.e. 4oC, 27oC, 32oC, 37oC, and 42oC. The parameters observed were the total LAB using the TPC (total plate count) method. The quality of the milk was carried out through organoleptic test, alcohol test, boiling test, pH tests, protein content tests. Qualitative data were analyzed descriptively, while quantitative data were analyzed using one-way ANOVA with Tukey's follow-up test with 95% confidence level. The results showed that the incubation period did not affect the quality of milk, however, it could affect the total LAB. In contrast, the incubation temperature can affect both.